2011
DOI: 10.1111/j.1537-2995.2011.03373.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular therapies supplement: the peritoneum as an ectopic site of hematopoiesis following in utero transplantation

Abstract: BACKGROUND In utero transplantation (IUT) has the potential to treat birth defects early before full development of the immune system. Relatively small grafts, that are not matched for major histocompatibility antigens, can be delivered even before onset of disease symptoms. IUT of hematopoietic stem cells is usually performed via intraperitoneal injection, yet the fate of donor cells in the peritoneal cavity is not fully understood. We review our recent work and present new data demonstrating that the periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…The inefficient migration of donor cells to the FL after i.p. IUHCT is supported by the study of Muench et al [35], which demonstrated that 62% and 50% of donor cells remained in the murine peritoneal cavity 24 hours and 1 week after IUHCT, respectively, with enriched HSCs. The persistence of donor cells in the perihepatic space and peritoneal cavity after i.h.…”
Section: Discussionmentioning
confidence: 90%
“…The inefficient migration of donor cells to the FL after i.p. IUHCT is supported by the study of Muench et al [35], which demonstrated that 62% and 50% of donor cells remained in the murine peritoneal cavity 24 hours and 1 week after IUHCT, respectively, with enriched HSCs. The persistence of donor cells in the perihepatic space and peritoneal cavity after i.h.…”
Section: Discussionmentioning
confidence: 90%
“…Many tissues, however, can accommodate hematopoiesis [ 23 ] and thus may contain the essential elements of a stem cell niche. EMH has been reported in such diverse tissues as the skin, joint, urinary bladder, peritoneum, pleura, testes, adrenal glands, and gastrointestinal tract [ 24 31 ]. Myelofibrosis, inflammation, and infection are frequent underlying causes of EMH.…”
Section: The Hspc Niche: the Bone Marrow And Beyondmentioning
confidence: 99%
“…Extramedullary hematopoiesis exists in different tissues and it is frequently correlated with myelopoiesis [Oliveira et al, 2007;Aguado et al, 2011;Muench et al, 2011]. Inside the peritoneal cavity, extramedullary hematopoiesis has been associated with case reports and clinical disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the peritoneal cavity supports extramedullary hematopoiesis in distinct situations [Holden et al, 2006;Muench et al, 2011], we investigated the capacity of these peritoneal stromal cells to support hematopoiesis using a coculture system. Bone marrow-derived hematopoietic cells were cultured with peritoneal stromal cells at passage 3.…”
Section: Stromal Peritoneal Cells Support Myelopoiesis In Vitromentioning
confidence: 99%